Ответ:
д) 3 1/6z+2/3z
3 1/6z+4/6z = 3 5/6 z Привели дробь 2/3 к общему знаменателю 4/6
е) 2 3/4t - 1 7/8t = 2 6/8t - 1 7/8t = 22/8t - 15/8t = 7/8t
ж) 5/18х + (5/12х-1/4х) = 5/18х+(5/12х-3/12х) = 5/18х+2/12х=5/18х+1/6х = 5/18х+3/18х = 8/18х=4/9х
з) 11/18n - (5/18n+1/6n) = 11/18n - (5/18n+3/18n) = 11/18n - 8/18n = 3/18n = 1/6n
и) 2/3c+1/9c-7/9c = 6/9c+1/9c-7/9c = 0
к) k - 1/7k = 7/7k - 1/7k = 6/7k
л) 3/11y+8/11y = 11/11y = y
м) 3/5 b+b = 1 3/5b
Пошаговое объяснение:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
д) 3 1/6z+2/3z
3 1/6z+4/6z = 3 5/6 z Привели дробь 2/3 к общему знаменателю 4/6
е) 2 3/4t - 1 7/8t = 2 6/8t - 1 7/8t = 22/8t - 15/8t = 7/8t
ж) 5/18х + (5/12х-1/4х) = 5/18х+(5/12х-3/12х) = 5/18х+2/12х=5/18х+1/6х = 5/18х+3/18х = 8/18х=4/9х
з) 11/18n - (5/18n+1/6n) = 11/18n - (5/18n+3/18n) = 11/18n - 8/18n = 3/18n = 1/6n
и) 2/3c+1/9c-7/9c = 6/9c+1/9c-7/9c = 0
к) k - 1/7k = 7/7k - 1/7k = 6/7k
л) 3/11y+8/11y = 11/11y = y
м) 3/5 b+b = 1 3/5b
Пошаговое объяснение: